Breathing Sense into Women’s Lives Shattered by War: Dah Theatre Belgrade - Olivera Simic (Law Text Culture, 2010)
The various ethnic and religious groups and individuals who suffered enormously during ethnic conflicts in the former Yugoslavia deal with the legacies of violence and human rights violations in a number of ways. As a human rights lawyer from this region, and someone who is scarred by the war, I have immersed myself in literature and art that explores armed conflict and its impact on women. After the dissolution of the former Yugoslavia, and since my arrival in Australia, I have been following closely the transitional justice processes in my homeland (such as trials and initiatives by local peace activists aimed at reconciliation) and have always been present — with my mind, heart and research — with peace activists from the former Yugoslavia in their struggle to address past atrocities. My particular experience affected my intellectual and spiritual being and has driven my academic work in the direction of the ongoing exploration of the causes and consequences of war in my homeland as well as the trauma, resilience and utmost courage of its people.